Neutrino masses through the seesaw mechanism in 3-3-1 models - Montero, J. C. [UNESP]; De, C. A. [UNESP]; Pleitez, V. [UNESP] (American Physical Society (APS), 2002)
Some years ago it was shown by Ma that in the context of the electroweak standard model there are, at the tree level, only three ways to generate small neutrino masses by the seesaw mechanism via one effective dimension-five operator. Here we extend this approach to 3-3-1 chiral models showing that in this case there are several dimension-five operators and we also consider their tree level realization.